2011
DOI: 10.3855/jidc.1847
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of rubella and immunogenicity following rubella vaccination in adolescent girls in India

Abstract: Introduction: Serologic surveys conducted in different countries indicate that rubella is a worldwide infection. Several such sero surveys conducted in India have also confirmed that 6-47% of women are susceptible to rubella infection. The current study was conducted on 1,329 female adolescents in 12 districts of Maharashtra, India, to assess their serological status in terms of rubella exposure. Methodology: After enrollment, a pre-vaccination blood sample was collected from the participants followed by rubel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 3 publications
1
15
0
Order By: Relevance
“…A seroprevalence rate of 67.3% was noted among girls in the age group of 11-18 years as reported by a study from Jammu and Kashmir, North India [8]. The seroprevalence of Rubellaspecific IgG antibodies appear to vary significantly with geographic locations, age, socioeconomic status, and the standards of living as evidenced by the reports from New Delhi, also a North Indian state with a 90% seroprevalence [9].…”
Section: Discussionmentioning
confidence: 72%
“…A seroprevalence rate of 67.3% was noted among girls in the age group of 11-18 years as reported by a study from Jammu and Kashmir, North India [8]. The seroprevalence of Rubellaspecific IgG antibodies appear to vary significantly with geographic locations, age, socioeconomic status, and the standards of living as evidenced by the reports from New Delhi, also a North Indian state with a 90% seroprevalence [9].…”
Section: Discussionmentioning
confidence: 72%
“…This figure is comparable with other published literatures from abroad. [20][21][22] The World Health Organization (WHO) established goals to eliminate rubella and CRS in the WHO Region of the Americas by 2010, the European Region by 2015, and in the WHO Western Pacific Region for accelerated rubella control and CRS elimination by 2015. Sustained vaccination strategy enabled America to decrease rubella cases by 98%, from 1,35,947 in 1998 to 2,998 in 2006.…”
Section: Discussionmentioning
confidence: 99%
“…Sharma et al reported that re-vaccination rubella immunity was 76% in 1359 Indian female children tested in 13 districts of Maharashtra state. After giving R-vac vaccine, 99.7% children developed antibodies to rubella 21. Studies on immunogenicity of MMR vaccine showed average 95% seroprevalence in children aged between 1 and 10 years in India after 5-year follow-up.…”
Section: Global Health Problem Analysismentioning
confidence: 99%